A new species of Dasypogon (Diptera: Asilidae) from Central Europe - Szczepański, Wojciech T. (Zootaxa, 2023)
Dasypogon is a widely distributed Palearctic genus. This contribution reviews the species from Central Europe. Two species are identified, including one new species—Dasypogon diabolicus sp. nov. An identification key of the Central European species and descriptions of the male and female of both species are provided along with illustrations of the habitus and male and female terminalia. An updated map with species distributions is presented, and a new corrected list of synonyms of D. diadema is proposed. The following new synonymy is established: Leptarthrus brevirostris (Meigen, 1804) = Dasypogon caudatus Bigot, 1881 syn. nov.